An evaluation of training delivery effectiveness of a program conducted by a private training company - N. Mohanasundram, Thangaraj (1998)
The aim of this study was to evaluate a series of a training programs called Effective Supervisor organized by a private training provider who is registered with the Human Resource Development Fund (HRDF) of the Ministry of Labour, Malaysia. The evaluation was undertaken by analysing perceived achievement of stated training objectives as measurement of training delivery effectiveness visa viscourse contents, trainer and external factors. The study was done by using secondary data, that is the questionnaires that have been filled by the participants of the programs 'Effective Supervisor' provided by Consembition Jaya Sdn Bhd. for the period between May 1996 and June 1998. The data collated for all the 151 participants over the seven sessions of the program between May 1996 and June 1998 were used in this study. This evaluation was basically a Kirkpatrick's Level One measurement carried out to assess the participants' reaction towards the training program.